Decoding ferroptosis in ischemic stroke: key genes and the therapeutic potential of acupuncture - Chunxiao Wu; Chunxiao Wu; Zhirui Xu; Qizhang Wang; Shuping Zhu; Chunzhi Tang (Frontiers in Aging Neuroscience)
BackgroundFerroptosis has been reported to be associated with the development of ischemic stroke; however, comprehensive investigations of ferroptosis-associated genes are lacking. Herein, key differentially expressed genes (DEGs) related to ferroptosis in ischemic stroke were identified and validated and the potential mechanism of acupuncture in treating ischemic stroke was explored through bioinformatics analysis and experiments.MethodsHigh-throughput RNA sequencing was performed to identify DEGs between cerebral ischemic injury tissue and normal brain tissue in mice. Subsequently, differentially expressed ferroptosis-related genes (DE-FRGs) were identified by intersecting the DEGs with a ferroptosis database. Functional enrichment analysis was conducted to investigate potential signaling pathways involved in ischemic stroke, while protein-protein interaction (PPI) analysis was used to explore interactions among the DE-FRGs. Hub genes were identified using the random forest algorithm, and their RNA expression levels were validated via RT-qPCR in sham-operated, MCAO model, and acupuncture groups.ResultsThe results showed that one hundred twenty-seven DE-FRGs were identified by comparing cerebral ischemic injury tissue with normal brain tissue in mice. KEGG enrichment analysis revealed that these DE-FRGs were primarily involved in the ferroptosis pathway, autophagy–animal pathway, apoptosis pathway, HIF-1 signaling pathway, and longevity-regulating pathway. The top 10 hub DE-FRGs selected through the PPI analysis and random forest algorithm included SLC3A2, FTH1, MAP1LC3A, SLC40A1, TFRC, TMSB4X NRAS CD82 CD44, and PTPN18. Nine genes were confirmed to be significantly differentially expressed between the sham and MCAO mouse models. Moreover, FTH1, SLC40A1, NRAS, CD82, and PTPN18 levels significantly increased after acupuncture in ischemic stroke mice.ConclusionThe ferroptosis pathway, autophagy–animal pathway, apoptosis pathway, HIF-1 signaling pathway, and longevity-regulating pathway were identified as crucial pathways associated with ferroptosis in cerebral ischemic stroke. Bioinformatics analysis and RT-qPCR suggested that FTH1, SLC40A1, NRAS, CD82, and PTPN18 might serve as potential key targets underlying the antiferroptotic effects of acupuncture on ischemic stroke.